Impact of Social Media Usage on Perception of Relationships and Mental Health Among Adolescents - Abbas, Salbia; Sheraz, Fatima; Mudassar, Nimra; Cheema, Nayab (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Adolescence represents a critical developmental stage where social interactions significantly impact well-being. The widespread adoption of social media platforms has fundamentally transformed how individuals communicate, interact, and perceive their environments. Purpose: Recent research seeks to clarify how social media affects adolescents' perceptions of relationships and mental health. Method: A purposive sampling method was used to involve 300 adolescents of both genders from urban and rural areas in this cross-sectional study. Data collection utilized a self-designed demographic questionnaire and standardized assessments, including the SMUS (Social Media Use Scale) developed by Tuck and Thompson (2023), PHQ-9 (Patient Health Questionnaire- 9) by Robert and W.H. (1991), and ARQ (Adult Relationship Questionnaire) by Scharf (1994). Both descriptive and inferential statistics were applied. Findings: The findings revealed a statistically significant negative correlation between social media use and mental health (r = - 0.163, p < 0.01), as well as perception of relationships (r = -0.196, p < 0.01), suggesting that increased social media use is associated with poorer mental health and diminished relationship perceptions. Linear regression analysis demonstrated that social media use significantly predicts lower mental health (B = -0.067, p < 0.05) and poorer perception of relationships (B = - 0.093, p < 0.05). Notably, excessive social media use emerged as a stronger predictor for decreased perception of relationships compared to mental health, indicated by the higher Beta "B" value for relationship perception. Conclusion: In conclusion, the study underscores the detrimental impact of excessive social media use on adolescents' mental health and relationship perceptions. Current research will be useful to integrating media literacy into educational curricula, launching public health campaigns, and equipping mental health professionals to effectively address issues related to social media use.